A Cross-Sectional Serological Study to Assess the Prevalence and Risk Factors of Anaplasmosis in Dromedary Camels in Punjab, Pakistan - Muhammad Zaeem Abbas; Muzafar Ghafoor; Muhammad Hammad Hussain; Mughees Aizaz Alvi; Tariq Jamil; Muhammad Sohail Sajid; Munazza Aslam; Ali Hassan; Shujaat Hussain; Mian Abdul Hafeez; Muhammad Irfan Ullah; Iahtasham Khan; et al. (Veterinary Sciences)
Anaplasmosis is an infectious disease transmitted by ticks and caused by obligate intracellular pathogen of belonging to genus Anaplasma Infections of one-humped camels (Camelus dromedarius) and llamas (Lama glama) have been reported previously. The aim of this study was to investigate the seroprevalence and risk factors of anti-Anaplasma spp. antibodies in Camelus dromedarius of the Punjab, Pakistan. A cross-sectional study was conducted during 2017–2018 to study the seroprevalence of anaplasmosis in Camelus dromedarius of 13 districts in Punjab province of Pakistan and to assess the associated risk factors including age, breed, gender, body condition score, tick infestation, location, season and management type. Serum samples from 728 camels (433 females and 295 males) were examined for anti-Anaplasma antibodies using a commercially available competitive enzyme-linked immunosorbent assay (cELISA) test kit. A univariable analysis was conducted and extended to multivariate logistic regression to find potential risk factors associated with the disease. Overall, the seroprevalence of anti-Anaplasma antibodies was 8.5% (8.5%, CI 6.6–10.8) with 62 positives in 728 camels. The highest seroprevalence was recorded for camels of the Central Punjab districts (16.1%, CI 11.5–21.7) followed by those of the Northwestern (5.4%, 2.8–9.3) and Southern Punjab (5.2%, 2.9–8.4) districts (p < 0.001). Multivariable analysis showed that location (Central Punjab: OR 2.78, p = 0.004), season (summer: OR 7.94, p = 0.009), body condition score (BCS 2: OR 14.81, p = 0.029) and tick infestation (OR 38.59, p < 0.001) are potential risk factors in the corresponding camel populations. The results showed that the camel population in Pakistan is seropositive for Anaplasma spp. The geographical zone, season, body condition and tick infestation were identified as significantly associated risk factors for seroprevalence of anaplasmosis in dromedary camels. To the best of our knowledge, the results of this current study provide the first evidence of exposure of camels to anaplasmosis in Pakistan. Molecular investigations in the future are highly recommended to determine the dynamics of the disease in camels.